Executive functions in post-traumatic stress disorder: their relation to PTSD severity and daily functioning - Safi, Nehal; Jahjah, Elias; Bergmann, Eyal; Fruchter, Eyal; Caspi, Yael; Oren, Udi; Josman, Naomi; Klinger, Evelyne; Engel-Yeger, Batya (Frontiers in Psychiatry, 2025)
BackgroundExecutive function difficulties may be prevalent in people with PTSD, and they might negatively affect their behavior and daily functioning. However, knowledge about the implications of executive function deficits on daily functioning and the assessments that reflect functional limitations is limited. This study aimed to measure how executive function difficulties affect daily functioning in PTSD using ecologically valid assessments that imitate daily activities.MethodsThe participants were 66 individuals aged 18–65 years: 26 diagnosed with PTSD and 40 healthy controls. All participants completed a socio-demographic questionnaire, the Clinician-Administered PTSD Scale, and the Behavior Rating Inventory of Executive Functions—BRIEF-A, a self-reported tool to assess the impact of executive functions on daily activities. The participants also performed a virtual shopping activity to assess executive functions while performing in a daily activity using the Virtual Action Planning Supermarket (VAP-S 2), a novel, ecologically valid, performance-based tool.ResultsDifficulties in executive functions were significantly more prevalent in PTSD patients: the BRIEF-A reflected how executive function difficulties manifested in behavioral dysregulation, restricting daily functioning. The VAP-S 2 revealed difficulties in executive functions, expressed as higher impulsivity, lower strategy use, and decreased performance efficiency while shopping in the virtual supermarket. Correlations were found between BRIEF-A and VAP-S 2: more collisions and lower inhibition in VAP-S 2 were correlated with worse BRIEF-A scores. Difficulties in executive functions correlated with PTSD severity.ConclusionsExecutive function difficulties in PTSD may correlate with PTSD severity and restrict daily functioning. Therefore, executive functions in PTSD should be evaluated using ecologically valid assessments to illuminate the implications of real-life activities. VAP-S 2 uniquely enables an objective assessment of executive functions in real-life scenarios for PTSD, complementing self-report and enhancing the ecological validity of findings. It is recommended to combine self-reports that reflect the person’s authentic perspective with performance-based assessments, such as the VAP-S 2, to focus intervention on people’s real-life context and, by that, improve their function and well-being.